39-8m=-(1+3m)

Simple and best practice solution for 39-8m=-(1+3m) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 39-8m=-(1+3m) equation:



39-8m=-(1+3m)
We move all terms to the left:
39-8m-(-(1+3m))=0
We add all the numbers together, and all the variables
-8m-(-(3m+1))+39=0
We calculate terms in parentheses: -(-(3m+1)), so:
-(3m+1)
We get rid of parentheses
-3m-1
Back to the equation:
-(-3m-1)
We get rid of parentheses
-8m+3m+1+39=0
We add all the numbers together, and all the variables
-5m+40=0
We move all terms containing m to the left, all other terms to the right
-5m=-40
m=-40/-5
m=+8

See similar equations:

| 60=b0.4 | | 3.5t=2/5 | | 3(t+1)=3(2t-3 | | 6(x+2)+2x=8(x-2)+8 | | -11=-11u | | -5(-7m-8)=9+4m | | x+49=-29 | | (6x+58)+(9x−1)=87 | | 8n+6=11n-30 | | 9+25=5+x | | -8(x+4)+39=16-9x | | 2x+10.5x=-10 | | 2x/3=12/15 | | -13=2b-b=10 | | 12-3x=-5x | | 3.5x=2/5 | | N-7=-(n-5) | | -237=-3(11+5x)-2x | | 0.3x+1.8=0.4(x+5)=0.2 | | -9x-1=-8x+15 | | 2x⁄3=12/15 | | 2x+10.5x=25 | | 2/1​ r−3=3(4−2/3​r) | | y+11=42 | | 3.2n+n=5 | | -387=-9(-5x+3) | | -5+6m=7 | | 12)-2=(n-8) | | -3(4a+4)=-108 | | 8(x-8)+2x=3(x-8)+11x | | m-30=35 | | 6x-8x=-2(x+2)+7 |

Equations solver categories